Persepsi Model Pembelajaran ADLX pada Mata Pelajaran Bahasa Indonesia SMP - Yolandini, Renilda Pratiwi; Patindra, Gani; Hasanah, Fidyatun (Prosiding Seminar Nasional Humaniora, 2025)
Indonesian language learning at the junior high school level is still often dominated by teacher-centered and traditional methods, which make students passive and slow in developing language skills. This study aims to explore students’ perceptions of the Active Deep Learning Xperience (ADLX) model in Indonesian language learning. A qualitative phenomenological approach was employed with Grade VIII students at SMP IT Ash-Shiddiiqi as participants. Data were collected through interviews, observations, and documentation, then analyzed thematically. The findings indicate that ADLX enhances student motivation, language skills, active participation, and self-confidence. It also creates a more interactive, collaborative, and reflective classroom atmosphere compared to conventional teaching. Theoretically, this study enriches the literature on active learning in the Indonesian educational context. Practically, it recommends that teachers consistently apply ADLX with adequate training and institutional support to optimize its effectiveness.   Abstract Pembelajaran Bahasa Indonesia di tingkat SMP masih sering berpusat pada guru dengan metode tradisional, sehingga siswa cenderung pasif dan keterampilan berbahasa berkembang lambat. Penelitian ini bertujuan menggali persepsi siswa terhadap penerapan model Active Deep Learning Xperience (ADLX) dalam pembelajaran Bahasa Indonesia. Penelitian menggunakan pendekatan kualitatif fenomenologis dengan partisipan siswa kelas VIII SMP IT Ash-Shiddiiqi. Data diperoleh melalui wawancara, observasi, dan dokumentasi, lalu dianalisis secara tematik. Hasil penelitian menunjukkan bahwa ADLX mampu meningkatkan motivasi, keterampilan berbahasa, partisipasi aktif, serta rasa percaya diri siswa. Suasana kelas menjadi lebih interaktif, kolaboratif, dan reflektif dibandingkan dengan pembelajaran tradisional. Secara teoretis, penelitian ini memperkaya kajian mengenai pembelajaran aktif dalam konteks Indonesia. Secara praktis, penelitian merekomendasikan penerapan ADLX secara konsisten oleh guru dengan dukungan pelatihan dan kebijakan sekolah yang memadai.